Guidelines for the Creation of Descriptors within the Archival Databases (Atlanti +, 2026)
Purpose: Descriptors represent an important tool in the process of creating objective information about archives, as most of the modern information processing systems are based on the descriptor system, which plays a key role. Descriptors represent an important access point for retrieval of information from archival information systems. They are the starting point for searching within the content and descriptions of archives therefore they must allow users the continuation of inquiries in archival information system. Practical experience gained through archival description, together with searching and retrieval within the Slovenian archival database has demonstrated a clear need for a more systematic treatment of the question of creation of headings. In particular, there is a need for guidelines governing the creation of subject headings and thesauri for archival content that can be applied consistently across different archival information systems and software platforms. Method/approach: To investigate this need, a comprehensive research project was conducted. Its primary objective was to develop practical guidelines for the formulation of subject headings and the establishment of thesauri applicable to archival records of enduring value, regardless of the software environment used for archival description. To identify the requirements for such guidelines, two complementary studies were undertaken. The first focused on users and patterns of use within the Slovenian cooperative archival database. The second study employed a qualitative research design based on content analysis. Selected domestic and international archival databases were examined using a predefined coding framework, which provided the basis for the analysis. The central research question was as follows: “Is the subject indexing of archival records implemented in a manner that enables users to conduct independent searches of archival databases and facilitates faster and easier access to archival records?” 1 Dr. Zdenka Semlič Rajh, Archival Councillor and Assocciate Professor at Alma Mater Europaea University, zdenka.semlic@almamater.si. GUIDELINES FOR THE CREATION OF DESCRIPTORS WITHIN THE ARCHIVAL DATABASES ZDENKA SEMLIČ RAJH 12 Results: The importance of names was confirmed not only by the analysis of Slovenian archival database but also by our examination of foreign archival information systems. Of the fifty-four systems analysed, only thirty-three supported descriptor-based searching. Among these, 89% enabled searching by personal names, 45% by family names, 63% by corporate body names, and 88% by geographical names. The results unequivocally confirmed the need for formal guidelines governing the formulation and application of descriptors. Conclusions/findings: On the basis of the analysis of records contained in Slovenian archival information systems, together with the identification of common theoretical principles, a set of guidelines was subsequently developed for the formulation of subject headings, thesauri, and classification structures within the Slovenian archival environment, particularly for the description of documentary and archival records.
Keywords: access; archives; access points; descriptors; subject headings